Effect of Seed Size of Afzelia quanzensis on Germination and Seedling Growth - Kupatsa Mtambalika; Chimuleke Munthali; Dominic Gondwe; Edward Missanjo (International Journal of Forestry Research)
Afzelia quanzensis Welw is a valuable timber producing tree species in Africa. A study was conducted to evaluate the influence of seed size on seed germination and seedlings quality of Afzelia quanzensis. Seed was categorized into three groups in regard to their length, small (<1.5 cm), medium (≥ 1.5 ≤ 2.5 cm), and large (>2.5 cm). The treatments were completely randomized into four replications. Germination percentage was not significantly (P>0.05) different between the treatments, although large seeds had the highest germination percentage of 94.9%. There were significant (P<0.05) differences in seedling height and root collar diameter among the different seed sizes, with large seeds having the highest seedlings height and largest root collar diameter. This was attributed to differences in the food reserves. Survival of transplants from shoot dieback was significantly (P<0.05) different such that seedlings from large seed attained the highest survival of 92%. It is therefore recommended that, for production of high quality transplants in the nursery, large seeds should be used.